Estudo e aplicações de probabilidade geométrica e paradoxos - Viana, Fernando Cesar de Abreu (2013)
This work, after a brief history and theory of probability, approaches the subject geometric probability. We believe it is an important branch of probability theory and we had the opportunity to present some examples. Initially, we studied the most famous problem in geometric probability, which is the problem of Bu on's needle. After a few years, the application of this problem allowed Allan MacLeod Cormack and Godfrey Newbold Houns eld, Nobel Prize winners in Medicine, the invention and development of computed tomography. This work also presents an interesting way to calculate areas of no elementary gures by using the geometric probability via the Monte Carlo Method. Another topic addressed concerns probabilistic paradoxes. The paradoxes presented are those which are contrary to common sense.